A Lifelong Call to Learn: Continuing Education for Religious Leaders - Reber, Robert E.; Roberts, D. Bruce (Rowman & Littlefield Publishers, 2009)
A Lifelong Call to Learn is aimed at directors of lifelong learning and continuing education that serve both clergy and laity in Catholic, Protestant, and Jewish seminaries and conference and retreat centers. While proposing new approaches in continuing theological education, it also addresses the need for programs that involve both clergy and laity at the congregational level and that support ongoing interreligious dialogue in our increasingly pluralistic society. The contributors to this book include seasoned practitioners as well as teachers and scholars in seminaries and universities from every part of the country in both denominational and ecumenical settings. The chapters explore historical perspective and educational contexts; theory and research in professional continuing education; innovations in continuing theological education; development, management, and promotion of programs; and directions and resources for the future. Particularly in this time of foment in theological education, when institutional leaders are striving to develop new models for the basic master of divinity degree, this collection will be of keen interest to theological educators in every setting.